Effect of deformation histories on texture evolution during equal- and dissimilar-channel angular pressing - Suh, JY; Han, JH; Oh, KH; Lee, JC (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
Finite element analyses and full constraint Taylor analyses based on the rate sensitivity model were performed to analyze deformation history and corresponding texture evolution during equal- and dissimilar-channel angular pressing, respectively. (C) 2003 Acta Materialia Inc. Published by Elsevier Science Ltd. All rights reserved.